2021
DOI: 10.1016/j.toxrep.2021.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum polysaccharides inhibit ischemia/reperfusion-induced myocardial injury via the Nrf2 antioxidant pathway

Abstract: Graphical abstract LBP attenuated myocardial ischemia/reperfusion injury by restoring redox status, ultimately improving cardiac function. CAT: catalase; GPX: glutathione peroxidase; HO1: heme oxygenase 1; IL-6: interleukin-6; I/R: ischemia/reperfusion; LBP: Lycium barbarum polysaccharides; Nrf2: nuclear factor erythroid 2-related factor 2; NQO1: NADPH dehydrogenase quinone 1; ROS: reactive oxygen species; SOD: superoxide dismutase; TNF-α: tumor necrosis factor α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This extension affected not only the median but also the maximum lifespan. Thus, this study joins others that have already shown a positive effect of algae and plant extracts in the Drosophila model [ 22 , 31 34 ]. To ensure that this is a true pharmacological effect and not a confounder based on reduced food intake, we investigated whether the extract affects food intake.…”
Section: Discussionsupporting
confidence: 81%
“…This extension affected not only the median but also the maximum lifespan. Thus, this study joins others that have already shown a positive effect of algae and plant extracts in the Drosophila model [ 22 , 31 34 ]. To ensure that this is a true pharmacological effect and not a confounder based on reduced food intake, we investigated whether the extract affects food intake.…”
Section: Discussionsupporting
confidence: 81%
“…Yang F. et al (2020) reported that LBPs dietary supplementation relieved oxidative stress in high fat diet-induced obese mice. Liu et al (2021b) found that LBPs supplementation reduced myocardial oxidative stress via activation of the nuclear factor erythroid-2 antioxidant signal pathway. Furthermore, plants containing flavonoids, phenolic compounds, ascorbic acid, and tocopherol were shown to exhibit antioxidant effects (Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Disruption of colon mucosa was profound with neutrophil infiltration, which was accompanied by the massive production of ROS and an increase in lipid peroxidation MDA levels [ 21 ]. As reported, LBP had antioxidative effects and could protect against the damage of lipid peroxidation induced by free radicals, and LBP could enhance nuclear factor-erythroid 2-related factor 2 (Nrf2) protein expression in ischemia/reperfusion-induced myocardial injury model [ 22 , 23 ]. Similar results were also found in our study, as treatment with LBP increased CAT activity and decreased MDA levels in serum.…”
Section: Discussionmentioning
confidence: 99%